The study of employee satisfaction in New Straits Times Press Berhad (NSTPB), Kuala Lumpur / Suhaida Laily Sulaiman - Sulaiman, Suhaida Laily (2009)
This study is a research of employee satisfaction in New Straits Times Press Berhad (NSTPB) whereby the researcher was in internship in the organization for five months to complete the study in Bachelor of Administration (Hons) Human Resource. The research is about the satisfactory of the employees towards the organization who worked for long years which explained their comfort zone in the organization and they do not have any intention to move out. Furthermore, this research explained the relationship between the independent variables and dependent variable which related to one and another. The independent variables consist of work dimension, pay dimension, promotion dimension and co-workers dimension has connected with the dependent variable which is the employee satisfaction. The employee satisfaction may be affected if any modifications have been made on those independent variables due to their linkage to each other and may influence the organization performance and publication in media press industry. The results of this research are based on the findings and analysis made using the Statistical Package for the Social Science Program (SPSS) and illustrates the verification between the dependent variable and independent variables. Literature reviews based on varies articles which are relevant to the study are included to verify and sustain that the research is valid. Conclusions and recommendations are comprehended for the organization to develop and improve in the upcoming future.